Hilarius Schmitt legal document and discharge papers - Schmitt, Hilarius, 1826-
Discharge papers from the Hessian army (1852 March 21) and legal document (1856 September 5) declaring Schmitt a citizen of the United States.
German soldier from Hesse-Kassel who later emigrated to Pennsylvania.
Collection material in German, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hesse-Kassel. -- Heer; Citizenship -- United States; Naturalization -- United States; Germany -- Emigration and immigration; United States -- Emigration and immigration; Soldiers